2021
DOI: 10.3389/fpls.2021.621587
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Hormonal Variations in Grapes of Irrigated and Non-irrigated Grapevines (Vitis vinifera cv. “Merlot”) Growing Under Mediterranean Field Conditions

Abstract: Agricultural practices in grapevines management include water restrictions due to its positive effect on wine quality, especially when applied at fruit ripening. Although the effects of water stress in some groups of phytohormones have already been described in leaves and whole grapes, information regarding tissue-specific variations in hormones during ripening in grapes is scarce. Field-grown grapevines from the cv. “Merlot” were subjected to two differential water supplies, including only rainfed, non-irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…These compounds act on the grape skin by dissolving the waxy components, which causes a high resistance to moisture transfer, and alkaline substances such as potassium carbonate (K 2 CO 3 ) facilitate the moisture transfer by breaking the skin [21]. Ribalta-Pizarro [22] reported that the hormone profile at the tissue level presented a differential accumulation of phytohormones during ripening in berry tissues, with the pulps being particularly poor in ABA, JA, and SA; seeds particularly accumulating ACC, gibberellins, and zeatin-type cytokinins; and the skin being particularly rich in auxin and active cytokinins. In this fashion, we can suggest that potassium carbonate, along with the high temperatures of the pretreatments for drying, led to an important decrease in hormones and the other studied compounds compared to the oak ash dipping solution.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds act on the grape skin by dissolving the waxy components, which causes a high resistance to moisture transfer, and alkaline substances such as potassium carbonate (K 2 CO 3 ) facilitate the moisture transfer by breaking the skin [21]. Ribalta-Pizarro [22] reported that the hormone profile at the tissue level presented a differential accumulation of phytohormones during ripening in berry tissues, with the pulps being particularly poor in ABA, JA, and SA; seeds particularly accumulating ACC, gibberellins, and zeatin-type cytokinins; and the skin being particularly rich in auxin and active cytokinins. In this fashion, we can suggest that potassium carbonate, along with the high temperatures of the pretreatments for drying, led to an important decrease in hormones and the other studied compounds compared to the oak ash dipping solution.…”
Section: Discussionmentioning
confidence: 99%
“…e late season dehydration can be attributed to dehydration and loss of berry cell vitality that results in losses of yield, quality, and profitability [11,30]. It has been observed that a severe water stress can originate a sharp decrease in both yield and grape quality, while a mild water stress can help to improve quality but usually decreasing yield [22,39]. e correlation analysis showed a strong negative relationship (r � −0.93) between grape yield and total anthocyanins per berry (Figure 7) as supported by Bindon et al [36], who observed inverse correlation, with total anthocyanins decreasing as yield increased.…”
Section: Berry Yield (Kg/vine)mentioning
confidence: 99%
“…However, if the tissue dehydration exceeds a critical level, a series of irreversible changes in the plant cause death [19]. Grapevines without water deficit has generally been found to cause a delay in ripening, possibly due to the accumulation of juice total soluble solids [20], the dilution effect of organic sugars in an increased berry size which is often associated with an increase in berry weight [21][22][23]. Generally, the effect of water stress on the ripening process may also due to a physiological response to an alteration in plant water status, which in turn impacts the regulation of pathways governing carbon metabolism in the berry [20].…”
Section: Introductionmentioning
confidence: 99%
“…Current studies have proved that the level of endogenous hormones in plants was not only affected by the climate 33 , but also by the cultivation environment and irrigation regime 34,43 . For examples, researchers found the ABA and ethylene signal components were differently accumulated in two distinct climates by analysing the transcriptional expression patterns of carotenoid metabolism in 'Cabernet Sauvignon' (Vitis vinifera L.) grapes 35 , further study also revealed that regulated de cit irrigation (RDI) could signi cantly improve ABA levels in 'Cabernet Sauvignon' (Vitis vinifera L.) wine grapes while reducing IAA levels 36 .…”
mentioning
confidence: 99%